Guanylin, Uroguanylin and Guanylate Cyclase-C Are Expressed in the Gastrointestinal Tract of Horses - Cappelli, Katia; Gialletti, Rodolfo; Tesei, Beniamino; Bassotti, Gabrio; Fettucciari, Katia; Capomaccio, Stefano; Bonfili, Laura; Cuccioloni, Massimiliano; Eleuteri, Anna Maria; Spaterna, Andrea; Laus, Fulvio (Frontiers in Physiology, 2019)
Guanylate cyclase-C (GC-C) is a multifunctional receptor, encoded by the GUCY2C gene, representing an attractive target for therapy in several gastrointestinal diseases in humans. Little is known about this system in horses. We investigated for the first time the gene expression of guanylin, uroguanylin and guanylate cyclase-C receptors in different horse’s gastrointestinal tracts. Tissue samples from stomach, duodenum, jejunum, ileum, head and body of cecum, left and right dorsal colon, left and right ventral colon, pelvic flexure, transverse colon, descending colon and rectum were collected from adult horses within one hour after the death. For each sample, total RNA was extracted from 100 mg of ground tissue and qRT-PCR performed on GUCA2a GUCA2b GUCY2 transcripts on CFX96 Touch instrument. Data analysis was carried out with Bio-Rad CFX Manager software and genes of interest normalized relative to the abundance of the two reference genes (SDHA, HPRT). Additionally, the protein expression levels of GC-C receptor have been analysed trough western blotting. A common pattern of expression throughout the gastrointestinal lumen for all three investigated transcripts was found. The expression of GUCA2a, GUCA2b and GUCY2 genes was higher in jejunum, ileum, descending colon and rectum. The levels of expression of GC-C protein confirmed these data. The findings of this study might open new scenarios for the therapeutic approach to enteric diseases of horse using selective agonists of GC-C.